“La mejor clase de física de mi vida”: perspectiva del maestro novato - Jimenez P., Yuly Lorena; Garnica, Yadir Alexander (Revista Científica, 2011)
This paper emphasizes the criteria that are at the basis of the argument of the beginning teachers for the Degree in Physics from the Universidad Distrital Francisco Jose de Caldas, to present their experiences in their physical best kind of living. The instrument to identify teachers' ideas is through an open trial, in which they describe their experiences spontaneously. It is intended then by means of an interpretation based on a qualitative and methodological approach to the teaching of physics to characterize some parameters to give a brief generalization affinities majority of students, selecting those most relevant and comparing the findings obtained in some research articulate teacher thinking paradigm and which establish an interpretative approach of the physics teacher discourse, especially on issues such as physical education, the role of teacher, student attitudes and activities of the class physics.